Wave Propagation and Radiation in Gyrotropic and Anisotropic Media - Eroglu, Abdullah; SpringerLink (Online service) (Boston, MA : Springer US : Imprint: Springer, 2010)
Wave Propagation and Radiation in Gyrotropic and Anisotropic Media fills the gap in the area of applied electromagnetics for the design of microwave and millimeter wave devices using composite structures where gyrotropic, anisotropic materials are used. The book provides engineers with the information on theory and practical skills they need to understand wave propagation and radiation characteristics of materials and the ability to design devices at higher frequencies with optimum device performance.
Wave Propagation and Dispersion Characteristics in Anisotropic Medium -- Wave Propagation and Dispersion Characteristics in Gyrotropic Medium -- Method of Dyadic Green$1 (Bs Functions -- Radiation in Anisotropic Medium -- Radiation in Gyrotropic Medium -- Wave Theory of Composite Layered Structures -- Microwave Devices Using Anisotropic and Gyrotropic Media.s
Keywords: Engineering; Physics; Magnetism; Microwaves; Engineering; Microwaves, RF and Optical Engineering; Magnetism, Magnetic Materials; Physics, general